Human papillomavirus infection among women attending family planning clinic in Nigeria: prevalence, correlates, and co-infection with Chlamydia trachomatis (2018)
Infection with high-risk genotypes of human papillomavirus (HPV) is considered the main cause of invasive cervical. A number of epidemiologic studies have suggested that HPV and Chlamydia trachomatis (CT) play a synergistic role in the etiology of cervical intraepithelial neoplasia and subsequent cervical cancer. The current study aimed to evaluate the HPV prevalence and the risk factors for co-infection with CT among women attending family planning clinic in Nigeria. Following enrolment, 90 patients were screened for IgG antibodies to virus-like proteins of HPV types 6, 8, 16, and 18. CT seropositivity was tested by enzyme-linked immunosorbent assay for the detection of IgG and IgM antibodies. The prevalence of HPV IgG was 20%. Seropositivity for CT IgM was 77.8% while the IgG was 0%. A total of 10 women (11.1%) were seropositive for both CT IgM and HPV IgG antibodies. Seropositivity for HPV IgG was significantly associated with age at marriage (P < 0.001), current Chlamydia infection (P < 0.011), and number of children (P < 0.025), while seropositivty for HPV IgG and Chlamydia trahomatis IgM was significantly associated with age at coitarche (P < 0.028), number of life sex partners (P < 0.033), and history of multiple sexual partners (P < 0.002).